Astaxanthin Promotes Nrf2/ARE Signaling to Alleviate Renal Fibronectin and Collagen IV Accumulation in Diabetic Rats - Xiaoyu Zhu; Yongjun Chen; Qing Chen; Huiyuan Yang; Xi Xie (Journal of Diabetes Research)
Astaxanthin (AST), a natural keto-carotenoid classified as a xanthophyll, is well known for its antioxidant properties. AST can ameliorate the pathological characteristics of diabetic nephropathy (DN). However, the underlying mechanisms remain to be explored. This study was aimed at exploring whether AST exerts a protective effect on DN via activating nuclear factor erythroid 2-related factor 2– (Nrf2–) antioxidative response element (ARE) signaling. Streptozotocin-induced diabetic rats were treated with AST for 12 weeks. We found that AST treatment ameliorated renal morphological injury. Reduced fibronectin and collagen IV protein expression were found in the kidneys of diabetic rats. Furthermore, AST promoted the nuclear translocation of Nrf2 and increased its downstream protein heme oxygenase-1 and superoxide dismutase 1 expression. AST also increased the activity of SOD and decreased malondialdehyde generation in the serum of diabetic rats. These results suggest that the renoprotective effect of AST on DN partly depends on Nrf2–ARE signaling. The antioxidative stress effect of AST is responsible for the activation of Nrf2–ARE signaling in DN.